Uncertainty analysis of eleven multisource soil moisture products in the third pole environment based on the three-corned hat method - Liu, J.; Chai, L.; Dong, J.; Zheng, D.; Wigneron, J.P.; Liu, S.; Zhou, J.; Xu, T.; Yang, S.; Song, Yongze; Qu, Y.; Lu, Z. (2021)
© 2020 Elsevier Inc.